2019
DOI: 10.3389/fpsyt.2019.00312
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Copy Number Raises the Potential of Left Frontopolar Hemodynamic Response as a Diagnostic Marker for Distinguishing Bipolar Disorder From Major Depressive Disorder

Abstract: Background: Given a lack of markers, diagnoses of bipolar disorder (BD) and major depressive disorder (MDD) rely on clinical assessment of symptoms. However, the depressive mood states of BD and depressive symptoms of MDD are often difficult to distinguish, which leads to misdiagnoses, which in turn leads to inadequate treatment. Previous studies have shown that the hemodynamic responses of the left frontopolar cortex measured by near-infrared spectroscopy (NIRS) differ between BD and MDD; these hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…A significant decreased mtDNAcn levels in manic patients was found in this study. The change of mtDNAcn was discussed in our previous report ( 28 ) and confirmed in later studies ( 56 , 57 ). To the best of our knowledge, this is the first study to explore the relationship between BDNF and mtDNAcn in BD.…”
Section: Discussionsupporting
confidence: 80%
“…A significant decreased mtDNAcn levels in manic patients was found in this study. The change of mtDNAcn was discussed in our previous report ( 28 ) and confirmed in later studies ( 56 , 57 ). To the best of our knowledge, this is the first study to explore the relationship between BDNF and mtDNAcn in BD.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding BD, there is an inconsistency in mtDNA copy number (mtDNAcn) studies that could be attributed to the diversity in clinical features, tissue types, and ethnicity. 71,[152][153][154][155] A recent meta-analysis identified no significant differences in mtDNAcn exhibited by BD patients or controls, while an Asian-specific meta-analysis for BD-mtDNAcn studies revealed significantly lower mtDNAcn in patients with BD, with a low level of heterogeneity. 155 Moreover, mtDNAcn was inversely correlated with the number of relapses of manic episodes.…”
Section: Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…Second, the demographic data used in our study were self-reported. Third, mtDNA copy number in leukocytes may modify the risk of several types of chronic diseases and conditions 1 23 as well as biobehavioral factors, but the direction and strength of each association differs significantly. Thus, it is difficult to determine the exact underlying cause of each observed association and its potential health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular epidemiologic studies have shown that mitochondrial DNA (mtDNA) copy number in leukocytes may modify the risk of several types of cancers 1 13 , diabetes 14 , 15 , cardiovascular disease 16 , 17 , and aging-related diseases 18 , 19 , as well as psychological disorders such as stress 20 , 21 and depression 22 , 23 . Thus, mtDNA copy number may serve as an important indicator of health.…”
Section: Introductionmentioning
confidence: 99%